Effect of steam explosion pre-treatment on methane generation from Ludwigia grandiflora. (November 2020) - Bhatia, Pranshu; Fujiwara, Masaaki; Ban, Syuhei; Toda, Tatsuki
Abstract: Overgrowth of water primrose ( Ludwigia grandiflora ) causes environmental problems worldwide. Anaerobic digestion of L. grandiflora is a low-cost treatment. However, lignin in the lignocellulose matrix of the biomass limits the anaerobic digestion process. Therefore, steam explosion was performed at 11 different severity factors with different combinations of temperature and retention time before anaerobic digestion to enhance the microbiological conversion of the lignocellulosic biomass. Increasing severity of the pre-treatment caused biomass solubilisation, which resulted in the production of inhibitors such as dissolved lignin and phenolic compounds. The maximum methane yield was 272.4 mL g-VS −1 at 165 °C for 30 min at a severity factor of 3.3, achieving a 3.2-fold increase compared to that of untreated biomass. At SF higher than 3.3 and temperature higher than 165 °C, the methane yield started decreasing, indicating the effect of inhibitors. Thus, steam explosion pre-treatment effectively enhanced the methane production of L. grandiflora despite its high lignin content and woody structure. Highlights: Ludwigia grandiflora was steam exploded at 120 °C−210 °C for 10, 30 and 60 min. Steam explosion increased methane yield by a 3.2-fold compared to that of untreated biomass. Increasing the pre-treatment severity induced substrate solubilisation. Substrate solubilisation caused higher inhibitor levels at higher severities.